IMPLEMENTASI METODE AGILE DAN FRAMEWORK LARAVEL PADA PENGEMBANGAN SISTEM INFORMASI BIMBINGAN SKRIPSI BERBASIS WEB - Rahman Rahman; Niswa Ayu Lestari; Hastuti Hastuti (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The rapid development of web technology can be used to automate various processes, including thesis guidance. The thesis guidance process in the Information Systems Study Program, Faculty of Science and Technology, is currently carried out by students coming directly to the supervisor by bringing printed documents. In the meeting, the lecturer provides revision points through a consultation sheet. However, this method has limited access to the results of the guidance and also has a negative impact on the environment. To overcome this obstacle, this study proposes the development of a "Web-Based Thesis Guidance Information System" which is expected to facilitate the guidance process more efficiently and documented. This study uses an applied research type that applies web technology with the Laravel Framework to design a thesis guidance system. The development of this system was carried out using the Agile method in four iterations, with each iteration lasting two weeks, so that the total development time reached eight weeks. The development stages include planning, design, development, testing, and deployment. The results of the study indicate that the system was successfully developed well, where all functionality was tested using the blackbox method and functioned according to the specified specifications, and was able to facilitate and document the thesis guidance process.